IMPLEMENTASI STRATEGI PENDIDIK DALAM MEMBENTUK NILAI KARAKTER PESERTA DIDIK DI SEKOLAH DASAR - Adilia, Fara; Rika Perdana , Dayu; Kembar Habibi, Roy; Mujiyati (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
Character buildingis a fundamental aspect of education at the elementaryschool level as it shapes students attitudes and behaviors. This study aims to describe the strategies implemented by teachers in developing students character values at SD Negeri 2 Bulu Rejo and to identify the supporting and inhibiting factors in the implementation process. This research employed a qualitative descriptive approach. The research subjects consisted of the principal and fifth-grade teacher. Data were collected through interviews, observations, and documentation. The data analysis techniques included data reduction, data display, and conclusion drawing. The findings reveal that character education strategies were integrated into daily school activities through role modeling, habituation, enforcement of school regulations, and contextual learning. The character values developed include religiosity, nationalism, independence, mutual cooperation, integrity, discipline, andresponsibility. Supporting factors include institutional commitment, active teacher involvement, and a conducive school environment. Meanwhile, inhibiting factors include differences in students family backgrounds, limited instructionaltime, and varying levels of student awareness. These findings indicate that character education requires collaboration between schools, teachers, and families to be implemented effectively and sustainably.